2016
DOI: 10.1016/j.biomaterials.2016.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Non-virally engineered human adipose mesenchymal stem cells produce BMP4, target brain tumors, and extend survival

Abstract: There is a need for enabling non-viral nanobiotechnology to allow safe and effective gene therapy and cell therapy, which can be utilized to treat devastating diseases such as brain cancer. Human adipose-derived mesenchymal stem cells (hAMSCs) display high anti-glioma tropism and represent a promising delivery vehicle for targeted brain tumor therapy. In this study, we demonstrate that non-viral, biodegradable polymeric nanoparticles (NPs) can be used to engineer hAMSCs with higher efficacy (75% of cells) than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 100 publications
(88 citation statements)
references
References 68 publications
0
81
2
1
Order By: Relevance
“…Polymeric gene delivery has the potential to address a wide variety of maladies through the delivery of exogenous DNA, siRNA, or miRNA but has been slow to translate from the benchtop to the clinic. Our group has demonstrated improved tumor survival following polymeric nanoparticle delivery of plasmid DNA specifically in an orthotopic brain cancer rat model via suicide gene delivery and through transfection of cancer‐honing mesenchymal stem cells that lead to a reduction in stem‐characteristics of tumor initiating cells . Other groups have demonstrated similar approaches for polymeric nanoparticle delivery of plasmid DNA in the lungs for treatment of cystic fibrosis, demonstrating the potential for clinical translation of polymeric particles for delivery of DNA.…”
Section: Discussionmentioning
confidence: 93%
“…Polymeric gene delivery has the potential to address a wide variety of maladies through the delivery of exogenous DNA, siRNA, or miRNA but has been slow to translate from the benchtop to the clinic. Our group has demonstrated improved tumor survival following polymeric nanoparticle delivery of plasmid DNA specifically in an orthotopic brain cancer rat model via suicide gene delivery and through transfection of cancer‐honing mesenchymal stem cells that lead to a reduction in stem‐characteristics of tumor initiating cells . Other groups have demonstrated similar approaches for polymeric nanoparticle delivery of plasmid DNA in the lungs for treatment of cystic fibrosis, demonstrating the potential for clinical translation of polymeric particles for delivery of DNA.…”
Section: Discussionmentioning
confidence: 93%
“…Nanoparticles formed at 30 w/w with the specific PBAE structure used were able to transfect less than 10% of ASCs, which was still greater than lipoplexes. Different PBAE structure may transfect ASCs with higher efficiency to enhance therapeutic effect, as shown by transfection screening of PBAE library on ASCs from a separate study [152]. A recent study reported that using PEI-pVEGF nanoparticles at N/P 7 in hyaluronic acid hydrogels with 60-μm pore led to 50% decrease in open diabetic wound area than non-porous hydrogels, possibly due to increased surface area contact for infiltrating host cells with released nanoparticles [153].…”
Section: Pro-angiogenesismentioning
confidence: 99%
“…NPs have been incorporated into stem cells spontaneously, through passive transport, or through active transport [8487]. They have also been used to manipulate MSCs to produce bone morphogenetic protein 4 (BMP4), thus avoiding the use of viral engineering in the delivery of antiproliferative agents [88]. Examples of stem-cell-based NP therapeutic systems against GBM include the silica nanorattle-doxorubicin nanoparticulate patch system in MSCs [57], the use of cytotoxic Fc-diOH-loaded MIAMI cells [59], and magnetic spinning disk NPs (SD)-loaded NSCs [56].…”
Section: Effector Functions Of Therapeutic Stem Cellsmentioning
confidence: 99%